MOISTURE SORPTION CHARACTERISTICS OF PINEAPPLE PROCESSING WASTE: SHELL AND CENTRAL CYLINDER - Vigano, Juliane [UNESP]; Gabas, Ana Lucia; Telis-Romero, Javier [UNESP] (Wiley-Blackwell, 2014)
The moisture adsorption isotherms of pineapple processing waste - shell and central cylinder - were determined at 40, 50, 60 and 70C using a gravimetric method. The sorption data were fitted to six well-known sorption isotherm models. The Guggenheim-Anderson-de Boer model was found to be the most satisfactory to represent the equilibrium moisture content data for the pineapple shells and central cylinders. The thermodynamic properties - differential enthalpy and entropy - were estimated by the Clausius-Clapeyron method. The differential enthalpy of the pineapple shells and central cylinders ranged between 11.486 to 1.671kJ/mol and 23.655 to -0.945kJ/mol, respectively. The differential entropy had minimum values at 0.04 and 0.005kg(water)/kg(dry solids) for the pineapple shells and central cylinders, respectively. The pineapple shells presented two lines of compensation, one controlled by entropy and the other controlled by enthalpy and the pineapple central cylinders showed only one zone controlled by enthalpy mechanisms.Practical ApplicationsThis work presents information about the moisture sorption characteristics of pineapple processing waste. This kind of information is important for designing the unit operations necessary in the waste process use. In addition, knowledge of the moisture sorption characteristics is useful with respect to selection of packaging materials and storage stability. In general, this work gives relationship between water activity, entropy, enthalpy and moisture content of pineapple processing waste.